2021
DOI: 10.1002/hed.26633
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐activated protein kinase inhibition‐induced modulation of epidermal growth factor receptor signaling in human head and neck squamous cell carcinoma

Abstract: Background Epidermal growth factor receptor (EGFR) overexpression is one of the most notable characteristics in head and neck squamous cell carcinoma (HNSCC). The MAPK kinase (MEK) inhibitor trametinib has shown efficacy to treat HNSCC; however, the molecular mechanism remains unclear. Methods HNSCC lines, mouse models, Western blot, and flow cytometry were employed to analyze the anticancer effects of trametinib. Results The JHU‐011, JHU‐022, and JHU‐029 HNSCC cells with different genetic alterations were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Our results align with YAP1 upregulation and AKT pathway activation and suggest the mechanism by which trametinib induces the AKT pathway activation via EGFR. To the best of our knowledge, there is only one study with contradictory results, that is, showing that a high dosage of trametinib reduced EGFR expression in three HNC cell lines through its effect on c‐MYC expression [34]. The differences between that study and the current study may derive from differences in cell lines, times of analysis, and concentrations of trametinib.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our results align with YAP1 upregulation and AKT pathway activation and suggest the mechanism by which trametinib induces the AKT pathway activation via EGFR. To the best of our knowledge, there is only one study with contradictory results, that is, showing that a high dosage of trametinib reduced EGFR expression in three HNC cell lines through its effect on c‐MYC expression [34]. The differences between that study and the current study may derive from differences in cell lines, times of analysis, and concentrations of trametinib.…”
Section: Discussionmentioning
confidence: 74%
“…Although mutations in key MAPK-pathway genes are infrequent in HNC patients, many HNC tumors rely on the MAPK pathway for proliferation and survival [9]. Several reports have shown that MAPK inhibition is potent in HNSCC models [11,19,[34][35][36][37][38]. Indications of the clinical potential of blocking the MAPK pathway were evident in a window-ofopportunity trial showing that trametinib induced tumor shrinkage in 65% of patients with HNSCC [18].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a wide range of biological functions, recent studies showed that activation of the Ras/Raf/MEK/ERK1/2 cascade is related to pathogenesis, progression, and oncogenic behavior of human cancer including breast and colorectal cancer, head and neck squamous cell carcinoma [13][14][15][16]. The main factor associated with the Ras/Raf/MEK/ERK1/2 pathway that promotes carcinogenesis is the hyperactivation of this cascade.…”
Section: Introductionmentioning
confidence: 99%